Association between the prudent dietary pattern and blood pressure in Chinese adults is partially mediated by body composition - Chen, Mengxue; Xu, Yujie; Wang, Xiaoyu; Shan, Shufang; Cheng, Guo (Frontiers in Nutrition, 2023)
High blood pressure or hypertension is one of the major risks of cardiovascular disease, which is the leading cause of death in China. This study aimed to assess the relationship between dietary patterns and blood pressure among Chinese adults. Using factor analysis of 66-item food frequency questionnaire to identify dietary patterns. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured according to standardized guidelines. Multivariate linear regressions were performed in 6849 Chinese adults (46.5% female) aged 21-70 years considering sociodemographic characteristics, lifestyle behaviors, and anthropometry data. The vegetable-rich pattern, animal-food pattern, and prudent dietary pattern were identified. After adjustment for potential confounders including age, gender, alcohol consumption, smoking status, energy intake, and physical activity, only prudent dietary pattern was negatively related to SBP (β=-2.30, p for trend =0.0003) and DBP (β=-1.44, p for trend =0.0006). Body mass index, waist circumstance and body fat percentage explained respectively 42.5%/47.8%, 14.8%/17.6% and 26.0%/29.1% of the association between prudent pattern and SBP/DBP in mediation analysis. There were no association were observed between other dietary patterns and blood pressure. In conclusion, Prudent dietary pattern was associated with lower SBP and DBP among Southwest Chinese and this association was partially explained by body composition.